Hubungan Kemampuan Berpikir Kreatif dan Sikap Terhadap Sains Dengan Literasi Sains Pada Siswa Kelas XI IPA MAN - Rusdi, Azimar; Sipahutar, Herbert; Syarifuddin, Syarifuddin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This research was intended to identify the correlation between (1) creative thinking and science literacy and (2) scientific attitude and science literacy in the concept of environment pollution. Sample was consisted of 219 eleventh grade science student of MAN Medan that was taken by cluster random sampling method. This study was encompassed phases preparation, action, and post research. The instrument were included to scientific literacy test, creative thinking test and scientific attitude questionary. The results is indicated that (1) there is positive correlation between creative thinking and science literacy with r=0.433 (2) there is positive correlation between science attitude and science literacy with r=0.363. (3) there is positive correlation between creative thinking and science attitude with science literacy with r=0,59. This study implies that reading comprehension and science attitude have important role to improve science literacy skill.